Adenosine Triphosphate Disodium Modified Hole Transport Layer for Efficient Inverted Perovskite Solar Cells. Issue 5 (30th March 2022) - Leng, Xuanye; Wan, Kaiwei; Wang, Hui; Wu, Guangbao; Zhang, Xuning; Liu, Yong; Han, Bing; Wang, Boxin; Zhang, Yuan; Zhou, Huiqiong; Tang, Zhiyong
Abstract: Interface engineering is an effectively method for high‐performance perovskite solar cells. Here, for the first time, we implemented a universal bio‐energy carrier‐adenosine triphosphate (ATP), in the form of adenosine triphosphate disodium (ATPS) on a conjugated polyelectrolytes poly [3‐(4‐carboxybutyl)thiophene‐2, 5‐diyl] sodium (P3CTS) hole transport layer (HTL) as a facile interfacial modification for efficient inverted perovskite solar cells. ATPS was explored to hold the capability to bridge the P3CTS HTL and the photo‐active perovskite, where the phosphate group of ATPS could passivate the uncoordinated Pb of perovskite via chelation while the adenine group could interact with the carboxyl group of P3CTS. An optimized and moderate band alignment was found in ATPS modified P3CTS HTL with subtle reduced valence band maximum (VBM). Meanwhile, the upper methylammonium lead halide (MAPbI3 ) perovskite layer on ATPS modified P3CTS HTL showed a superior film quality with larger crystal size and less surface defects. Accordingly, bimolecular recombination was found to be dominant associated to the reduced charge carrier recombination in the ATPS device while the charge extraction across HTL/perovskite interface was also apparently facilitated. As a result, the ATPS modified photovoltaic device exhibited an open current voltage (Voc ) of around 1.10 V and power conversion efficiency (PCE) of 20.15%. Furthermore, the shelf stability of the ATPS device is much superior with almost no decay after 3 months (>2000 h), while only 75% of the original PCE maintained for the control. The work provides a facile interfacial strategy utilizing biomaterials towards efficient and stable perovskite solar cells. Abstract : Bio‐energy carrier adenosine triphosphate (ATP) disodium was the first‐time applied as interfacial modification bridge layer for high performance invert perovskite solar cell. Noteworthily, the phosphate group in ATP disodium can passivate uncoordinated Pb and thus reduces the charge carrier loss across the perovskite solar cell. The ATP disodium modified pure methylammonium lead halide (MAPbI3 ) based solar cell exhibited a power conversion efficiency (PCE) of 20.15% with enhanced device stability.